2008
DOI: 10.1177/0748730407311110
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Melatonin Regulates Seasonal Changes in Song Control Nuclei of the House Sparrow,Passer domesticus: Independence from Gonads and Circadian Entrainment

Abstract: Avian behavior and physiology are temporally regulated by a complex circadian clock on both a daily and an annual basis. The circadian secretion of the hormone melatonin is a critical component of the regulation of circadian/daily processes in passerine birds, but there is little evidence that the gland regulates annual changes in primary reproductive function. Here it is shown that locomotor rhythms of house sparrows, Passer domesticus, which are made arrhythmic by either pinealectomy or maintenance in consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…rhythm in song and call behaviors has only recently been shown (Wang et al, 2012), even though melatonin influence on song nuclei volume and the expression of melatonin receptors in song nuclei has been well documented (Bentley, 2003;Bentley and Ball, 2000;Bentley et al, 1999;Bentley et al, 2013;Cassone et al, 1995;Cassone et al, 2008;Gahr and Kosar, 1996;Jansen et al, 2005;Whitfield-Rucker and Cassone, 1996). Additionally, melatonin inhibited the spontaneous firing rate of a vocal premotor nucleus in the zebra finch, suggesting that it can act directly on vocal circuits to influence vocal patterning (Jansen et al, 2005).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…rhythm in song and call behaviors has only recently been shown (Wang et al, 2012), even though melatonin influence on song nuclei volume and the expression of melatonin receptors in song nuclei has been well documented (Bentley, 2003;Bentley and Ball, 2000;Bentley et al, 1999;Bentley et al, 2013;Cassone et al, 1995;Cassone et al, 2008;Gahr and Kosar, 1996;Jansen et al, 2005;Whitfield-Rucker and Cassone, 1996). Additionally, melatonin inhibited the spontaneous firing rate of a vocal premotor nucleus in the zebra finch, suggesting that it can act directly on vocal circuits to influence vocal patterning (Jansen et al, 2005).…”
Section: Research Articlementioning
confidence: 99%
“…The short duration of nocturnal melatonin experienced under long days would lead to the prediction that melatonin is inhibitory to courtship behaviors, while being nocturnally active during peak diel levels of melatonin would lead to the inverse prediction. In support of an inhibitory role of melatonin in vocalization of diurnally active species, melatonin treatment in songbirds mimics the effect of short days by decreasing song nuclei volumes (Bentley et al, 1999;Cassone et al, 2008). Furthermore, daily melatonin treatment in pinealectomized zebra finches kept in constant dim light entrained song and call activity to occur during periods without melatonin (Wang et al, 2012).…”
Section: Melatonin Regulation Of Vocal Excitabilitymentioning
confidence: 99%
“…First, melatonin can stimulate cell mediated immune responses typical of winter, while increasing daylength dampens the immune system during reproduction (Bentley et al 1998 ). Second, melatonin can directly affect the plasticity of the avian song control system (Bentley et al 1999; Cassone et al 2008 ). In particular, melatonin receptors have been identified in the forebrain song control nucleus, Area X.…”
Section: Light and Circadian Rhythmsmentioning
confidence: 99%
“…Studies on avian melatonin receptors mainly focused on the retina (Rada and Wiechmann, 2006), gonads (Aste et al, 2001) and song-control nuclei in the brain (Cassone et al, 2008;Whitfield-Rucker and Cassone, 1996) photoreception takes place in the retina only and there has been an evolutionary loss of two retinal cone classes (Barrett et al, 2003) and of certain opsins which are found in nonmammalian vertebrates including birds and fishes (Bellingham et al, 2003). These differences in circadian organisation are believed to be the consequence of a "nocturnal bottleneck" during early evolution of mammals (Foster et al, 1993).…”
Section: Discussionmentioning
confidence: 99%